Sideways moves to adult life: the transnational mobility and transitions of young Italians to Australia. - Marchetti, Giulia; Baldassar, Loretta; Harris, Anita; Robertson, Shanthi (Journal of Ethnic & Migration Studies, 2024)
Since the Global Financial Crisis, Italy has become (again) a country of emigration for young people, with over one million Italians aged 18–34 living abroad [Fondazione Migrantes, ed. 2019. Rapporto Italiani nel Mondo 2019. Roma: Tau Editrice]. As the country of the 'long family', transitions to adulthood in Italy feature a distinctive, prolonged and late move out of the parental home. Transnational mobility thus provides not only an escape from high youth unemployment and economic stagnation, but allows young Italians to craft new ways to make an independent adult life. Drawing on in-depth interviews with 25 young Italians in Australia, we show how transnational mobility intersects with transitions to adulthood, focusing on experiences of independent dwelling and career trajectories in a unique, non-EU context. We argue that trajectories towards adulthood can be altered, anticipated, delayed and suspended by transnational mobility, and that young Italians actively renegotiate family expectations and migration requirements as they build 'adult' lives. While Australia's relative economic stability provides opportunities for transitions 'blocked' in Italy, both adulthood and settlement are seldom fixed arrival points, and young people flexibly reconfigure their pathways as they navigate a complex immigration policy environment. Further, despite the freedom that considerable distance from family provides, transnational intergenerational relationships remain an important influence.